Effects of geodesic dome trajectories on the specific strength of composite overwrapped pressure vessels: FE modelling. (29th April 2023) - Coskun, Taner; Sahin, Omer Sinan
Abstract: In this study, it was aimed to find out geodesic dome trajectories of composite overwrapped pressure vessels, and investigate the effect of dome profiles on the structural performances. In this context, geodesic paths for 0.2, 0.3, 0.4, 0.5 and 0.6 dimensionless polar opening radii were determined by solving elliptical integrals and filament winding angles were calculated throughout the dome and cylindrical portions. Afterward, finite element analysis was performed to obtain mechanical properties by using the Ansys ACP module. As a result of the current study, it has been concluded that dome profile and filament winding angle are highly dependent on the polar opening radii. When the performance factor was considered, it has been determined that the optimum pressure vessel has 0.6 dimensionless polar opening radii. Moreover, it was observed that minimum equivalent stress, strain, deformation and inverse reverse factors have occurred in the pressure vessel with 0.6 dimensionless polar opening radii. Furthermore, it was showed that effective parameters in the mechanical performance of pressure vessels can be optimized to obtain strengthened and lighter structures. Highlights: Structural responses of the COPVs with various geodesic dome trajectories were studied. Geodesic dome trajectory was found to be quite effective on the performance factor of COPVs. 69.4% improvement was achieved in performance factor with ascending polar opening radii. Dome parts were generally strengthened with ascending polar opening radii.